2008
DOI: 10.1161/circresaha.107.157099
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Importance of Glycosylation in Thrombin Activatable Fibrinolysis Inhibitor

Abstract: Abstract-Activated Thrombin Activatable Fibrinolysis Inhibitor (TAFIa) exerts an antifibrinolytic effect by removing C-terminal lysines from partially degraded fibrin. These lysines are essential for a rapid conversion of plasminogen to plasmin by tissue type plasminogen activator. TAFI is heavily glycosylated at Asn 22 , Asn 51 , Asn 63 , and Asn 86 . Although the glycans occurring at the glycosylation sites have previously been identified, the biochemical role of these glycans is not known yet. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…The specific activity (expressed as units per milligram) of TAFIa was evaluated at 22°C using the chromogenic assay and a standard of hippuric acid, spanning a concentration range from 16M to 2mM to quantify the amount of hippuric acid formed during the substrate reaction. 21 …”
Section: Ma-tck26d6mentioning
confidence: 99%
“…The specific activity (expressed as units per milligram) of TAFIa was evaluated at 22°C using the chromogenic assay and a standard of hippuric acid, spanning a concentration range from 16M to 2mM to quantify the amount of hippuric acid formed during the substrate reaction. 21 …”
Section: Ma-tck26d6mentioning
confidence: 99%
“…Inhibition of Intrinsic TAFI Activity by Protein InhibitorsThe ability of PCI, LCI, and TCI to inhibit the intrinsic TAFI activity was analyzed as described previously (19,21). Briefly, 15 l of TAFI (0.37 M, final concentration) in 50 mM Tris-HCl, pH 7.5 was titrated using PCI, LCI, or TCI (ranging from 0 to 50 M, final concentration).…”
Section: Methodsmentioning
confidence: 99%
“…This is the only MCP pro-domain that is glycosylated, thus suggesting biological significance. In this context, it has been speculated that the carbohydrates aid in stabilization and solubility of the enzyme and may affect the intrinsic proteolytic activity (15,19). In addition, the majority of the identified transglutaminase amine acceptor sites are also located in the pro-domain, thus enabling TAFI to be cross-linked to other proteins during coagulation/fibrinolysis (18,20,21).…”
mentioning
confidence: 99%
“…In the article published by Buelens et al 14 in this issue of Circulation Research, the authors report the construction, expression, and characterization of several mutants of TAFI missing 1 or more N-linked glycosylation sites. This type of posttranslational modification may also influence many of the biochemical properties of the proteins, such as stability, dynamics, and ligand binding.…”
mentioning
confidence: 99%
“…20 Moreover, N-glycosylation is crucial during the normal processing of human coagulation factor VII. 21 Finally, N-linked glycosylation is important in determining molecular weight, thrombin cleavage, and functional activity of human protein S. 22 Using an elegant approach, Buelens et al 14 have determined the biochemical importance of the glycosylation of TAFI. From their data it can be concluded that it is mainly the glycosylation at Asn86 that contributes to the biochemical properties of TAFI.…”
mentioning
confidence: 99%